The Influence of the Social Support on Symptoms of Anxiety and Depression among Patients with Silicosis - Bing Han; Bo Yan; Jian Zhang; Na Zhao; Jinkai Sun; Chao Li; Xibing Lei; Hongbo Liu; Jie Chen (The Scientific World Journal)
The improvement of social support promotes the mental health and improves the health status. The study aimed to examine the influence of the social support on symptoms of anxiety and depression among patients with silicosis and provide the scientific basis to further alleviate anxiety and depression and to monitor their whole quality of life. We investigated 324 inpatients with silicosis between April 2011 and September 2011. The HADS (the Hospital Anxiety-Depression Scale) was the major methodology used to evaluate anxiety and depression, and the MSPSS (the Multidimensional Scale of Perceived Social Support) to evaluate the social support level. Among patients with silicosis, 99.1% had anxiety symptoms, and 86.1% had depression symptoms. Meanwhile, the social support significantly influenced symptoms of anxiety and depression. The study suggested that patients with silicosis presented more anxiety and depression symptoms, while the social support levels of the patients were relatively low. The influence of social support on symptoms of anxiety and depression among patients with silicosis implied that improving the level of social support and the effective symptomatic treatment might alleviate anxiety and depression symptoms and improve physical and mental status.